HISTORY OF THE DEVELOPMENT OF THE TRANSPORTATION SYSTEM OF UZBEKISTAN (1945-1990) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
Today, the transport system occupies a special place in the world market. It is natural that service is an important factor of economic stability. From the first days of the establishment of Soviet power, the most important task was to manage the economy and end private ownership.